A fast-growing, painless, solid scrotal mass. Issue 11 (November 2015) - Franklin, Abbey; VanderBrink, Brian; DeFoor, William R.
Abstract : ABSTRACT: The history and physical examination of an adolescent male are critical to early detection of scrotal abnormalities. Although rare, paratesticular rhabdomyosarcoma grows quickly and can be life-threatening. This article focuses on the importance of prompt recognition, diagnosis, and appropriate management of paratesticular rhabdomyosarcoma in an adolescent.